Pengaruh Perbedaan Pola Asuh Orang Tua Terhadap Motivasi Akademik Mahasiswa Perantauan - Ireene, Ireene; Agustina, Agustina (Peneliti.net, 2024)
The world of education is experiencing rapid development which is also accompanied by an increase in the number of students studying in various universities. During their education, they often have to live away from their parents as migrant students. One of the factors that influence their experience during their education is academic motivation. Academic motivation is a separate concern because it is closely related to academic achievement itself. Academic motivation is not only influenced by the academic environment itself, but also starts from the family environment. Parenting is the main factor of concern in the study. How parents raise their children can also affect academic motivation, especially how the parenting style has a prolonged influence so that it still has an impact on children even though they live away from their parents. The formulation of the problem of this research itself is